1986
DOI: 10.1152/jappl.1986.61.3.1018
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory changes induced by prolonged laryngeal stimulation in awake piglets

Abstract: To examine the role of the laryngeal reflex in modulating cardiorespiratory function, we stimulated the superior laryngeal nerves (SLN) bilaterally in unanesthetized, chronically instrumented piglets (n = 10, age 5-14 days). The SLN were placed in cuff electrodes and wires were exteriorized in the neck for stimulation. A cannula placed in the aorta was used for blood pressure recording and arterial blood sampling. During each experiment, 1-2 days after surgery, ventilation was recorded using whole-body plethys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…reflexes evoked regardless of the cause of the apnea. Furthermore, we have previously shown that SLN stimulation in unanesthetized piglets resulted in no significant change in heart rate or blood pressure (28). Similarly, herein SLN stimulation in the presence of hyperoxia had a negligible effect on heart rate or blood pressure (Table 2).…”
Section: Apnea and Hypertension Hypertension Developed In Syn-mentioning
confidence: 70%
“…reflexes evoked regardless of the cause of the apnea. Furthermore, we have previously shown that SLN stimulation in unanesthetized piglets resulted in no significant change in heart rate or blood pressure (28). Similarly, herein SLN stimulation in the presence of hyperoxia had a negligible effect on heart rate or blood pressure (Table 2).…”
Section: Apnea and Hypertension Hypertension Developed In Syn-mentioning
confidence: 70%
“…This result is consistent with a study in unanesthetized rabbits in which SLN stimulation, with intensity at 1.2-1.5 times the threshold for inducing swallowing reflex (0.2 ms, 0.2-0.65 mA, 30 Hz), that did not affect the behavior of the animal [14]. In unanesthetized piglets, when SLNs were stimulated (0.5 ms, 10 Hz) with an intensity near threshold for respiratory changes, which were lower than that for producing discomfort behavior, mean respiratory frequency decreased by 57% during stimulation period of 5 min or 1 h [6,7]. When SLN electrical stimulation was applied to conscious humans, sensation of touch and pain were induced, depending on stimulation parameters [15].…”
Section: Discussionmentioning
confidence: 88%
“…The purpose of this study was to progress from acute stimulation in anaesthetized animals and to establish a conscious experimental animal model to translate results obtained in anesthetized animals for potential clinical application in osteoporosis. The SLN is known to include afferent nerve fibers that can inhibit respiration [6][7][8]. Therefore, it is necessary to identify parameters that do not adversely affect respiratory measures by SLN stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Preferential suppression of expiratory efforts by increasing depth of anesthesia is similarly imminent threat to the unanesthetized awake animals. 19 This apnoeic response to airway irritation observed in anesthetized subjects whose tracheas were stimulated with water injection. 4 Therefore, the types appears to be more pronounced in neonatal animals than adult animals.…”
Section: Stimulation In Awake Subjectsmentioning
confidence: 97%